Nursery fertilization affects seedling traits but not field performance in Quercus suber L. - Trubat, R; CORTINA, J; Vilagrosa, A (Journal of Arid Environments, 2010)
The success of forest plantations in areas subjected to seasonal drought is strongly dependent on seedling traits. However, there is no consensus on the set of plant traits determining establishment success in these environments. We hypothesize that traits associated with nutritional stress, such as reduced biomass allocation and changes in root morphology, may promote seedling resistance to drought. We tested this hypothesis by assessing the effect of different fertilizer types and doses on the morphology and ﬁeld survival of Q. suber seedlings. This hypothesis had been previously tested with ﬁve Mediterranean species in a semi-arid environment. Nutrient deprivation decreased total biomass accumulation and slenderness ratio (ratio between stem height and root collar diameter). Nitrogen deprivation increased biomass allocation and decreased root growth potential. Short-term seedling survival was not related to nutritional regimes, seedling size or root growth potential. Differences in stem height between control seedlings and those subjected to nutrient manipulations increased in the ﬁeld as a result of shoot dieback and scarce growth. In contrast, differences in root collar diameter gradually vanished. Nutrient management in the nursery showed a strong potential for modifying the morphology of Q. suber seedlings but the relationship between these changes and seedling survival remains elusive
Keywords: functional attributes; nutrient deprivation; root growth potential; seedling establishment; seedling quality

Fertilización tardía y establecimiento de Quercus ilex subsp. ballota 2/11 - CORTINA, J; MONERRIS, J; DISANTE, K; FUENTES, D; Valdecantos, a (V Congreso Forestal Español, 2009)
La restauración de ecosistemas mediterráneos con frecuencia requiere la reintroducción de especies leñosas. Pero existe una gran incertidumbre sobre las características que debe reunir un brinzal para aumentar sus probabilidades de éxito en el campo. Algunos estudios han mostrado que la fertilización en vivero permite una mayor supervivencia y crecimiento en campo. Sin embargo, en estos experimentos, las variaciones en el estado nutricional no se pueden desligar de los cambios morfológicos que promueve la fertilización. Para evaluar la importancia del estado nutricional, frente a las variaciones morfológicas inducidas por éste, hemos evaluado el comportamiento en el campo de brinzales de una savia de Quercus ilex subsp. ballota no fertilizados y brinzales a los que se aplicó fertilización tardía (posterior a la parada otoñal de crecimiento de la parte aérea). Nuestras hipótesis son: (i) la fertilización tardía permite mejorar el estado nutricional de los brinzales sin variar su tamaño y (ii) con ello, se aumenta la supervivencia y el crecimiento de los brinzales en el campo. La fertilización tardía no afectó al tamaño de los brinzales, pero mejoró su estado nutricional. En campo, la supervivencia fue muy elevada antes del primer verano (>98%), disminuyendo después del mismo hasta un rango de valores de 65-100%. En ningún caso la supervivencia estuvo relacionada con la fertilización en vivero. Por el contrario, la tasa de crecimiento antes del verano fue inferior en plantas no fertilizadas, invirtiéndose esta tendencia durante el verano. La tasa anual de crecimiento fue superior en las plantas fertilizadas, confirmando parcialmente nuestra hipótesis. La fertilización tardía representa una técnica sencilla para reducir el uso de fertilizantes en vivero, produciendo brinzales de pequeño tamaño pero elevada capacidad de respuesta en campo. Palabras
Keywords: cultivo en vivero; encinares; estado nutricional; Quercus rotundifolia; restauración forestal

Una nueva técnica viverística para la introducción de plantones de DE QUERCUS SPP. EN CLIMA SECO Y SEMIÁRIDO - Vilagrosa, A; SEVA, J P; Valdecantos, a; HERNÁNDEZ, N; CORTINA, J; Bellot, J; Vallejo, V R (II Congreso Forestal Español, 1997)
We present a new technique to improve the establishment of Quercus spp. seedlings in dry and semiarid environments. It is based on the use of pre-germinated acorns transplanted in biodegradable nursery container which are transferred to the field befo re root pruning and upward root growth occurs. In this experiment we also tested the use of tree-shelters.
Keywords: bellotas pregerminadas (voyant); clima mediterráneo; plantones; Quercus spp.; supervivencia